Herpes Labialis and Oral Candidiasis in HIV-infected intravenous drug users with poor hematologic status - Sufiawati, Irna; Sasanti, Harum (Padjadjaran Journal of Dentistry, 2008)
Hematologic abnormalities are common in HIV-infected patient, particularly in individuals with more advanced HIV disease. Hematologic abnormalities and their association with HIV-associated oral lesions had been reported. Intravenous drug use has been associated with increased oral lesions too. We reported a case of oral lesions in a 24 years old man HIV-infected intravenous drug users. Poor hematologic status is a risk factor of Oral Candidiasis in HIV-infected person with clinical features appear generally. But the clinical feature of Herpes Labialis is not usually because of his poor hematologic status. Itâs concluded that poor hematologic status and transmission of HIV through contaminated needlestick are the high-risk factors of oral lesions and appear not usually clinical features in ODHA. Correction of these hematologic abnormalities and appropriately management of oral lesions can minimize the severity and increase the better quality of life patient.